Fine-tuning of Th17 Cytokines in Periodontal Disease by IL-10. (September 2015) - Moretti, S.; Bartolommei, L.; Galosi, C.; Renga, G.; Oikonomou, V.; Zamparini, F.; Ricci, G.; Borghi, M.; Puccetti, M.; Piobbico, D.; Eramo, S.; Conti, C.; et al.
Periodontitis (PD) is a chronic disease caused by the host inflammatory response to bacteria colonizing the oral cavity. In addition to tolerance to oral microbiome, a fine-tuned balance of IL-10 levels is critical to efficiently mount antimicrobial resistance without causing immunopathology. Clinical and animal studies support that adaptive T-helper (Th) cytokines are involved in the pathogenesis of alveolar bone destruction in PD. However, it remains unclear what type of Th response is related to human PD progression and what role IL-10 has on this process. We addressed the contribution of IL-10 in limiting Th1 and Th17 inflammatory response in murine and human PD. Through a combination of basic and translational approaches involving selected cytokine-deficient mice as well as human genetic epidemiology, our results demonstrate the requirement for IL-10 in fine-tuning the levels of Th17 (IL-17A and IL-17F) cytokines in experimental and human PD. Of novelty, we found that IL-17F correlated with protection in murine and human PD and was positively regulated by IL-10. To our knowledge, this is the first demonstration of the protective role for IL-17F in PD, its positive regulation by IL-10, and the potential differential role for IL-17A and IL-17F in periodontal disease.